2003
DOI: 10.1159/000072562
|View full text |Cite
|
Sign up to set email alerts
|

Design and Baseline Characteristics of the Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) Study

Abstract: Evidence suggests that statin therapy reduces the risk of stroke in patients with coronary heart disease (CHD), but its benefit for patients with cerebrovascular disease and no history of CHD remains uncertain. The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) Study is a prospective, multi-centre, double-blind, randomised, placebo-controlled trial designed to evaluate the effects of atorvastatin 80 mg/day in patients who previously experienced a stroke or transient ischaemic attack, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The mean age of patients (67 years) and the preponderance of males are in accordance with other recent trials of secondary prevention such as the Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL), the Management of Atherothrombosis with Clopidogrel in High-Risk Patients with Recent Transient Ischaemic Attack or Ischaemic Stroke (MATCH), and the Prevention Regimen for Effectively Avoiding Second Strokes (PRoFESS) (table 4) [17,18,19,20], and are reasonably consistent with data from hospital registries and stroke incidence studies [21,22,23]. As the recurrence of stroke is highest during the first month after the first event, the investigators were encouraged to enroll patients as early as possible, once they were stabilized.…”
Section: Discussionsupporting
confidence: 78%
“…The mean age of patients (67 years) and the preponderance of males are in accordance with other recent trials of secondary prevention such as the Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL), the Management of Atherothrombosis with Clopidogrel in High-Risk Patients with Recent Transient Ischaemic Attack or Ischaemic Stroke (MATCH), and the Prevention Regimen for Effectively Avoiding Second Strokes (PRoFESS) (table 4) [17,18,19,20], and are reasonably consistent with data from hospital registries and stroke incidence studies [21,22,23]. As the recurrence of stroke is highest during the first month after the first event, the investigators were encouraged to enroll patients as early as possible, once they were stabilized.…”
Section: Discussionsupporting
confidence: 78%
“…The SPARCL trial is currently investigating this issue [68]. Pertinent to patients with WMH, the Cardiovascular Health Study examined the association of statin drug use with changes in white matter measures on serial MRI scans separated by 5 years, and found no notable differences in evolution of white matter measures between treatment (statin vs. no statin) groups [69].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…The Stroke Prevention by Aggressive Reduction of Cholesterol Levels (SPARCL) study demonstrated the positive effects of statin therapy also in secondary prevention of cerebrovascular diseases [13, 38, 39] and these positive results support a change in clinical guidelines for patients with stroke or transient ischemic attack (TIA).…”
Section: Stroke Prevention and Statinsmentioning
confidence: 99%
“…Patients were eligible for the study if they had had a previous TIA or stroke, had an LDL level between 100 mg/dl (2.58 mmol/l) and 190 mg/dl (4.91 mmol/l), and no evidence of coronary artery disease. The primary clinical endpoint was the time to first occurrence of a fatal or nonfatal stroke [38, 39]. In this study, 4,731 patients who had had a stroke or TIA within the past 6 months were randomized.…”
Section: Statins and Secondary Prevention Of Strokementioning
confidence: 99%